Mobile Accident Notification - MEVLÜT INAN; Rıdvan SARAÇOĞLU (International Journal of Applied Methods in Electronics and Computers, 2016)
Traffic accidents are one of the most important and serious problems, our country encounters. As the percentage of injured and casualties in traffic accidents are huge in numbers, it causes thousands of people injured or dead in a year. In the situation of coming by a traffic accident that we face commonly in daily life, generally people directly use their mobile phones and call the related units. However, as the required, right and adequate information is not given to these related units, the cases may sometimes end with casualties. One of the most important reasons of casualties in car accidents is the wrong, senseless first aids performed to the victims of injuries by surrenders. In this study, the aim is to determine the exact location of the accident with its latitude and longitude that is determined automatically via the application present in the responsive citizen who tries to help the victims of the accident. With this system named as “Mobile Accident Notification” the users are aimed to send accident notification in online or via sending message when there is no internet access with the help of mobile applications that process in Android Operating System. These accident data kept in remote server are monitored on web pages or Android mobile phones. In this thesis, a web-based, open-source accident filtration system was developed and the accidents were provided to be monitored by the authorized people in related units.